Menstrual hygiene: knowledge and practice among adolescent school girls in rural settings - Kapoor, Gitanjali; Kumar, Dinesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Menstrual hygiene is an issue that every girl and women must deal within her life, but there is lack of awareness on the process of menstruation and proper requirements for managing menstruation among adolescent girls. The objectives of present study are to assess the knowledge and the practices of menstrual hygiene among the rural school going adolescent girls and to assess the restrictions practiced by adolescent school going girls during menstruation. Methods: It was a community based cross-sectional study. The present study was undertaken among the adolescent school going girls in the Govt. Higher Secondary School in Marh block of Jammu district. 132 girls of the 8th, 9th, 10th, 11th and 12th standard of the school was selected for the study. A predesigned, pretested and structured questionnaire was used in the study. The data collection technique was a personnel interview of the study subjects. Results: The mean age of menarche in the study subjects was 13.43 years. It was evident that only 65 (49.24%) of the participants were aware about menstruation before menarche and the most important source of the information about menstruation for them was found to be their mothers. 59.09% girls used sanitary pads only, 27.27% used new cloth and 13.64% used old washed cloth. 98.48% of the respondents followed some restriction or taboo during menstruation. 93.18% had daily bath. Regular hand washing was present in 90.91% subjects of which 86.36% subjects used soap and water for hand washing. Regular cleaning of the external genitalia was present in 65.91% subjects only, of which 66.67% used soap and water and 33.33% used only water. Conclusions: There is a need to educate the girls about menstruation, its importance and hygiene maintenance; to enable them to lead a healthy reproductive life in future.